Influence of internal and external factors on the introduction of e-business and e-marketing in agribusiness - Stojoska, Sanja; Nacka, Marina (Faculty of Agricultural Sciences and Food - Skopje, 2022)
The emergence of the Internet, the rise of technology and economic globalization stimulate changes in companies’ operations, including the inevitable changes in the marketing strategy. One of the main trends in modern marketing is focus on the Internet and social media as most significant tools for promotion. As in traditional marketing, in electronic marketing there are also internal and external factors that influence its implementation.The aim of this research is to analyse the various internal and external factors that influence the introduction of E-Marketing to companies’ operations. The sample includes 76 small and medium enterprises(SMEs) from the agribusiness sector in North Macedonia, interviewed with a structured questionnaire. Four groups of factors were isolated, and a detailed explanation was provided of the various aspects that affect the implementation of E-Marketing within the companies.Resultsshowed that the acceptance of E-marketing by agrobusiness SMEs in North Macedonia is significantly affected by the third parties, customers, competitors,and suppliers. Although some E-Marketing tools are already being continuously used, it was noticed a lack of IT capabilities and insufficient management support. Most respondents rated high the need for E-Marketing, with an emphasis on the significant online presence of buyers. The obtained results are especially important for companies that want to encourage an initiative for E-Marketing introduction. It is apparent that there is awareness of E-marketing, yet the companies have to direct their human, financial and technological resources to facilitate the introduction of new technologies and attain support by management and professional team
Keywords: internet, e-marketing, e-business, factors, technology